2003
DOI: 10.3168/jds.s0022-0302(03)73979-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationship Between Body Condition Score, Dairy Character, Mastitis, and Diseases Other than Mastitis in First-Parity Danish Holstein Cows

Abstract: The aim of this study was to explore the possibilities of using body condition score (BCS) or dairy character (DC) as indicators of mastitis and diseases other than mastitis in first-parity Danish Holsteins. The dataset included 28,948 observations on conformation scores and 365,136 disease observations. The analysis was performed using a multitrait linear sire model. Heritability estimates for BCS and DC were moderate (0.25 and 0.22), and heritability estimates for mastitis and diseases other than mastitis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
58
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 23 publications
12
58
1
2
Order By: Relevance
“…This seems to indicate that cows with a genetically high BCS 1) would have a greater chance to have a calf that survives (CSm) and 2) would transmit genes to the calf that permit an easy birth (CEd) and increased chance of survival (CSd). These last statements are supported by previous research that reported that genetically low BCS was related to less robust cows presenting impaired fertility (Dechow et al, 2001;Pryce et al, 2001) or health disorders such as mastitis (Lassen et al, 2003;Neuenschwander et al, 2009). …”
Section: Genetic Correlations Between Bcs and Calving Traitssupporting
confidence: 77%
“…This seems to indicate that cows with a genetically high BCS 1) would have a greater chance to have a calf that survives (CSm) and 2) would transmit genes to the calf that permit an easy birth (CEd) and increased chance of survival (CSd). These last statements are supported by previous research that reported that genetically low BCS was related to less robust cows presenting impaired fertility (Dechow et al, 2001;Pryce et al, 2001) or health disorders such as mastitis (Lassen et al, 2003;Neuenschwander et al, 2009). …”
Section: Genetic Correlations Between Bcs and Calving Traitssupporting
confidence: 77%
“…Although the difference in mastitis incidence between thin and not-thin cows was small, the thin cows were expected to have a greater incidence. Typically, very fat or very thin cows are at a greater risk of disease in the first 100 DIM (Lassen et al, 2003). Figure 6 is the plot of convergence of the average daily genetic correlation between BCS and mastitis calculated by using genetic (co)variance estimates from every fifth round of the Gibbs sampler.…”
Section: Resultsmentioning
confidence: 99%
“…Th e relationship between dairy character and mastitis incidence was addressed in some previous studies. Hansen et al (2002) and Lassen et al (2003) estimated moderate genetic correlations between these two traits in Danish Holstein cattle and concluded that breeding for less expressed dairy character will increase resistance to mastitis. We had no data on CM, but assuming that SCS is a good indicator of mastitis, no such a tendency as in Danish Holsteins was observed in the Polish population.…”
Section: Discussionmentioning
confidence: 99%